[SAP 10.2 – updates for heat networks : Covering proposals to natural-gas CHP, the Products Characteristics Database, Biomass and recovered heat factors].: Covering proposals to natural-gas CHP, the Products Characteristics Database, Biomass and recovered heat factors]. Heat networks, including those with Combined Heat and Power (CHP) and those that use recovered heat. Appendix C, (2021) - Unknown
No abstract available